2018
DOI: 10.1007/s11306-018-1362-8
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS analysis of the ruminal metabolome response to thiamine supplementation during high grain feeding in dairy cows

Abstract: IntroductionThiamine is known to attenuate high-concentrate diet induced subacute ruminal acidosis (SARA) in dairy cows, however, the underlying mechanisms remain unclear.ObjectivesThe major objective of this study was to investigate the metabolic mechanisms of thiamine supplementation on high-concentrate diet induced SARA.MethodsSix multiparous, rumen-fistulated Holstein cows were used in a replicated 3 × 3 Latin square design. The treatments included a control diet (CON; 20% starch, dry matter basis), a SARA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 30 publications
6
34
0
Order By: Relevance
“…Hence, the level of 5-methoxyindole-3-acetic acid in Group H with higher protein diets was signi cantly higher than that in Group C. In this study, catechol as an antioxidant [72,73] was positively related to the relative abundances of Ruminococcus_2 and Prevotella_1, which might imply that high energy and protein levels in Group H could enhance the catechol concentration by these two genera. Xue et al [74] reported that the content of spermidine increased in the group of high concentrate diets compared with moderate concentration of diets, which is in line with our study. Furthermore, correlation analysis in this study revealed that spermidine had high positive relationships…”
Section: Comparison Of the Composition And Differences Of Ruminal Metsupporting
confidence: 93%
“…Hence, the level of 5-methoxyindole-3-acetic acid in Group H with higher protein diets was signi cantly higher than that in Group C. In this study, catechol as an antioxidant [72,73] was positively related to the relative abundances of Ruminococcus_2 and Prevotella_1, which might imply that high energy and protein levels in Group H could enhance the catechol concentration by these two genera. Xue et al [74] reported that the content of spermidine increased in the group of high concentrate diets compared with moderate concentration of diets, which is in line with our study. Furthermore, correlation analysis in this study revealed that spermidine had high positive relationships…”
Section: Comparison Of the Composition And Differences Of Ruminal Metsupporting
confidence: 93%
“…Hernández et al (2014) reported a significant increase in the rumen VFA concentration (150-225 mM) of the caws under ruminal acidosis [6]. Previous studies have reported that in acidosis lipopolysaccharide (LPS) derived from the rumen down-regulates stearoyl-CoA desaturase 1 expression (SCD1) and demonstrated up-regulation of the genes involved fatty acid β-oxidation [10]. The present results of the gene expression profile assay indicated the obvious pattern as up-regulation of the genes CPT1A, ALDH9A1and TSPAN12, associated with the fatty acid oxidation and down-regulation of SCD (stearoyl-CoA 9-desaturase) in the acidosis group.…”
Section: Discussionmentioning
confidence: 99%
“…System level understanding of the bovine metabolism and relationship with their products is essential in cow breeding. However, several in vivo studies have demonstrated changes in some genes expression within the rumen tissue in response to the acidosis, but the functional and molecular host mechanisms are mostly unknown [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that thiamine supplementation could effectively attenuate subacute ruminal acidosis (SARA) induced by a high-grain diet through buffering ruminal pH, shifting rumen fermentation pattern, and balancing the structure of ruminal microorganisms [12,13]. Thiamine (C 12 H 16 N 4 OS), also known as vitamin B1, plays a critical role in carbohydrate metabolism [14] and has been proved to be the co-enzyme of pyruvate formate-lyase (PFL) which promotes pyruvate hydrolyzing into acetyl-CoA and reduces the accumulation of lactate [13]. The promoted reaction of pyruvate to acetyl-CoA may benefit ruminal carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%